2007
DOI: 10.1016/j.jpaa.2006.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Hankel planes

Abstract: Starting from an (m +1)×(n +1) matrix A one can construct (m + p+1)×(n +1)( p+1) block Toeplitz matrices T ρ A ( p), p ≥ 0, based on the rows of A. The connections between the ranks of the two matrices is studied by comparing the corresponding vector spaces of row relations R and R( p). A main tool are the Hankel matrices with rows in R. The dimension of R( p) is determined in terms of geometric invariants attached to the Hankel matrices with rows in R. The study of Hankel r -planes of P m , for r ≥ 1, turns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
4
Order By: Relevance
“…Через G( , ) обозначим грассманиан -плоскостей в проективном пространстве P = P( ). Рассматривается значимое подмногообразие грассманиана G( , ), которое называется многообразием Ханкеля, обозначается как ( , ) и было впервые введено в работе [1]; ( , ) -это многообразие -плоскостей Ханкеля в P , которое при < − 2 является собственным подмногообразием грассманиана G( , ) ⊆ P , = (︀ +1 +1 )︀ − 1 (более подробно, см. [1]).…”
Section: г файллаunclassified
See 2 more Smart Citations
“…Через G( , ) обозначим грассманиан -плоскостей в проективном пространстве P = P( ). Рассматривается значимое подмногообразие грассманиана G( , ), которое называется многообразием Ханкеля, обозначается как ( , ) и было впервые введено в работе [1]; ( , ) -это многообразие -плоскостей Ханкеля в P , которое при < − 2 является собственным подмногообразием грассманиана G( , ) ⊆ P , = (︀ +1 +1 )︀ − 1 (более подробно, см. [1]).…”
Section: г файллаunclassified
“…Если представить -плоскость в терминах матрицы размера ( + 1) × ( + 1), то основной областью деятельности будет теория операторов, в частности, операторов Тёплица (см. [2]); в работе [1] плоскости Ханкеля появляются при изучении структуры модуля Рао кривых, лежащих на гладкой квадрике. Плоскости Ханкеля связаны со стандартной рациональной нормальной кривой ⊆ P , т.е.…”
Section: г файллаunclassified
See 1 more Smart Citation
“…A (r + 1) × (m + 1) matrix M = (m ij ) with complex entries m ij = m i+1 j−1 = a i+j−2 , that is, A Hankel matrix may not have independent rows, but by our definition Hankel r-planes are always represented by Hankel matrices of maximal rank. In [2] the definition of a Hankel r-plane only requires the rows of a Hankel matrix to be contained in the r-plane. In that case it is shown that a Hankel r-plane L = P(V ) is disjoint from C m if and only if there exists a unique Hankel matrix M whose r + 1 rows span V (cf.…”
mentioning
confidence: 99%
“…In that case it is shown that a Hankel r-plane L = P(V ) is disjoint from C m if and only if there exists a unique Hankel matrix M whose r + 1 rows span V (cf. [2,Proposition 4.11]), and that when r m − 2 every r-plane is Hankel (cf. [2,Remark 4.2]).…”
mentioning
confidence: 99%